2012
DOI: 10.1167/iovs.12-10350
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Vision of Youths with Low Vision: Motion Perception, Crowding, and Visual Search

Abstract: Our results reveal a complex pattern of visual deficits in peripheral vision and indicate a significant role of attentional mechanisms in observed impairments. These deficits were not adequately captured by measures of foveal function, arguing for the importance of independently assessing peripheral visual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…We reported a detailed analysis of pre-training results in a previous paper32. In brief, pre-training results revealed low central acuity for motion, deficits in motion perception that increased with increasing visual eccentricity, large impairments in the visual search ability and moderate deficits in visual crowding.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We reported a detailed analysis of pre-training results in a previous paper32. In brief, pre-training results revealed low central acuity for motion, deficits in motion perception that increased with increasing visual eccentricity, large impairments in the visual search ability and moderate deficits in visual crowding.…”
Section: Resultsmentioning
confidence: 95%
“…This, in turn, places additional demands on dynamic control of visuomotor mechanisms, which may be particularly important in peripheral vision2829. LV is often associated with a characteristic reduction in attention to peripheral visual fields, even when there is no known impairment to this region303132; impairments of either the central or peripheral fields often reduce visual performance in using other regions3334. This suggests that some of the impairments observed in LV might reflect higher-level attentional deficits—deficits that might be particularly amendable via action video game training.…”
mentioning
confidence: 99%
“…This deficit could also be one of the underlying causes of longer search times in children with visual impairments. 13,14,20 Other studies have shown that children with visual impairments need more time to perform fine motor tasks. 33 Although the tasks in our study did not require a complicated motor response, problems with fine motor skills could have resulted in longer reaction times for some of the children.…”
Section: Relation To Previous Researchmentioning
confidence: 99%
“…8,10,11 Thus, the WHO definition of visual impairment may be too narrow for children with CVI, as well as for children with other visual impairments. [12][13][14] Presently, clinical tests of visual function do not assess visual processing speed. However, nontimed visual acuity tests may not reflect the demands of daily life activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation